Are children's voices heard when dealing with child safeguarding concerns? Audit of clinical records in a CAMH service in one district. (24th May 2012) - Dave, A; Rao, V
Abstract : Background: Good practice around child safeguarding involves taking children's views into account alongside a whole family approach. However there is little evidence of how often this directive is followed in clinical practice. A review of case notes in a CAMH service (part of inter-agency audit under section 11 (WT) requirements) addressed this issue recently. Aims: To ascertain: a) Whether children's views were taken into consideration when dealing with safeguarding concerns; b) Whether a 'whole-family approach' was adopted around safeguarding issues. Methods: Retrospective audit of clinical records by two named safeguarding professionals in the borough. 96 case notes, representing 10% of cases open to the service, were reviewed. In 36 notes (37.5%) safeguarding concerns were recorded; these were reviewed in detail. Each set of records was assessed using a traffic light system. Red (unacceptable standard of practice), Amber (acceptable practice, nearing standards). Green (practice met or exceeded standards). Results: Overall, service was rated amber for both questions. Other interesting observations: ▶ Lack of narrative records. ▶ Difficult to locate sections in the notes regarding safeguarding concerns, referral and subsequent actions. ▶ Practice rated as 'red' did not lead to serious risks due to protective mechanisms - supervision and MDT discussions. Conclusions: ▶ There was little recording of the children's voice in the notes; ▶ Strong emphasis on parent's / carers' views. ▶ Whole family therapeutic approaches are a core part of CAMHS work but this was not seen to be applied to safeguarding issues. Recommendations: ▶ Safeguarding referrals and notes should be recorded in a separate, colour-coded section of case notes. ▶ Encourage practice of consciously recording children's views separate from parents'. Encourage reflective practice and discerning application of knowledge around safeguarding ▶ Use family therapy approaches to deal with safeguarding concerns. ▶ Implement identified training needs. ▶ Share and cascade good practice in monthly meetings with named and designated leads. ▶ Re-audit.